DESAIN DAN PENGEMBANGAN MESIN MICRO-PRESS PEMBENTUK KOMPONEN MIKRO - Asep Indra Komara; Aida Mahmudah; Adinda Sri Lestari; Johanes C. J. Hasibuan (Jurnal Rekayasa Mesin, 2022)
The increasing application of micro electro mechanical systems technology on daily life devices increases the need for micro components. Furthermore, it must be supported by reliable fabrication technology to produce micro-sized products. One of these technologies is micro-sheet metal forming, which is a forming technology from sheet metal with 10-300µm thickness. The development of this technology requires a special press machine that is used in the scope of micro-scale work, named micro-press. Micro-press is still rare due to it was used for individual experiment purposes. Thus, it is necessary to develop the micro-press to support research and manufacturing of micro-part. In this study, the design of a micro-press is intended to accommodate the miniaturization problems and to be easy in fabrication and re-fabrication. Then, the micro-press will contribute to fulfill the micro-parts need. By using the VDI 2222 design method, the design of a 5kN micro-press machine with a servo motor drive is obtained, and validation of construction strength was carried out with the help of the appropriate CAE software. The results of the design validation show that the construction of the micro-press machine is quite strong. The selected component has a strength specification that is greater than required, and the maximum stress that occurs in the frame, which is 80.096 N/mm2, is still very lower than the allowable stress on the SPHC material. The magnitude of the resultant displacement shows a fairly small value, i.e. 0.178 mm.